Farming Performance of Farm Women in Rice Based Farming Systems of Andhra Pradesh - P. Vijaya Lakshmi; K.S. Purnima (Journal of Agricultural Extension Management, 2016)
The study was conducted in three districts, one from each region of undivided Andhra Pradesh. Three mandals from each selected district and two villages from each selected mandal were chosen. Ten farm women were chosen randomly from each village thus making a total sample of 180 farm women equally selected from three categories i.e., Large, Medium and Small based on their farm size, based on stratified random sampling. The farming performance of farm women in rice based farming systems of the three regions was analysed using six selected indicators, viz., cropping intensity, crop yield index, milk yield index, level of adoption, commercialization index, and expansion I diversification index. The findings revealed that there was significant difference in the mean scores among the three categories of farm women in respect of overall performance. In other words, the large category farm women had the highest mean score of 395.0 followed by medium farm women (378.86). The small farm women had the least mean score of 373.62 in respect of overall farming performance.